Neurologic and Functional Morbidity in Critically Ill Children With Bronchiolitis*. Issue 12 (December 2017) - Shein, Steven L.; Slain, Katherine N.; Clayton, Jason A.; McKee, Bryan; Rotta, Alexandre T.; Wilson-Costello, Deanne
Abstract : Objectives: Neurologic and functional morbidity occurs in ~30% of PICU survivors, and young children may be at particular risk. Bronchiolitis is a common indication for PICU admission among children less than 2 years old. Two single-center studies suggest that greater than 10–25% of critical bronchiolitis survivors have neurologic and functional morbidity but those estimates are 20 years old. We aimed to estimate the burden of neurologic and functional morbidity among more recent bronchiolitis patients using two large, multicenter databases. Design: Analysis of the Pediatric Health Information System and the Virtual Pediatric databases. Setting: Forty-eight U.S. children's hospitals (Pediatric Health Information System) and 40 international (mostly United States) children's hospitals (Virtual Pediatric Systems). Patients: Previously healthy PICU patients less than 2 years old admitted with bronchiolitis between 2009 and 2015 who survived and did not require extracorporeal membrane oxygenation or cardiopulmonary resuscitation. Interventions: None. Neurologic and functional morbidity was defined as a Pediatric Overall Performance Category greater than 1 at PICU discharge (Virtual Pediatric Systems subjects), or a subsequent hospital encounter involving developmental delay, feeding tubes, MRI of the brain, neurologist evaluation, or rehabilitation services (Pediatric Health Information System subjects). Measurements and Main Results: Among 3, 751 Virtual Pediatric Systems subjects and 9, 516 Pediatric Health Information System subjects, ~20% of patients received mechanical ventilation. Evidence of neurologic and functional morbidity was present at PICU discharge in 707 Virtual Pediatric Systems subjects (18.6%) and more chronically in 1, 104 Pediatric Health Information System subjects (11.6%). In both cohorts, neurologic and functional morbidity was more common in subjects receiving mechanical ventilation (27.5% vs 16.5% in Virtual Pediatric Systems; 14.5% vs 11.1% in Pediatric Health Information System; both p < 0.001). In multivariate models also including demographics, use of mechanical ventilation was the only variable that was associated with increased neurologic and functional morbidity in both cohorts. Conclusions: In two large, multicenter databases, neurologic and functional morbidity was common among previously healthy children admitted to the PICU with bronchiolitis. Prospective studies are needed to measure neurologic and functional outcomes using more precise metrics. Identification of modifiable risk factors may subsequently lead to improved outcomes from this common PICU condition. Abstract : Supplemental Digital Content is available in the text.